2011
DOI: 10.1111/j.1442-2018.2011.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women who have a vaginal birth after requesting a Cesarean section due to a fear of birth: A biographical, narrative, interpretative study

Abstract: A fear of childbirth is a reason for a Cesarean section on request without a medical indication. The law for patients' rights in Norway does not give women the opportunity to choose a Cesarean section, only the potential to participate in the decision-making process. This requires cooperation between health professionals and patients. The present study explores the experience of women who had a vaginal birth after requesting a Cesarean section due to a fear of birth. A biographical, narrative, interpretative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“… USA, Americas Urban 16 Non-pregnant women Community a In-depth interviews C Shorten [ 46 ] Internet-based decision aid about birth choices after previous caesarean developed from an earlier paper-based decision aid. USA, Americas Urban 9 Pregnant women 5 Semi-structured Interviews B Ramvi [ 45 ] Women who took part in a team Midwifery intervention referred because they requested a caesarean because of fear of birth and actually had a vaginal birth. Norway, European Urban 5 Postnatal women 1–5 In-depth interviews A Basso [ 44 ] Problematizing educational intervention with groups of pregnant women and partners comprising eight face-to-face sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… USA, Americas Urban 16 Non-pregnant women Community a In-depth interviews C Shorten [ 46 ] Internet-based decision aid about birth choices after previous caesarean developed from an earlier paper-based decision aid. USA, Americas Urban 9 Pregnant women 5 Semi-structured Interviews B Ramvi [ 45 ] Women who took part in a team Midwifery intervention referred because they requested a caesarean because of fear of birth and actually had a vaginal birth. Norway, European Urban 5 Postnatal women 1–5 In-depth interviews A Basso [ 44 ] Problematizing educational intervention with groups of pregnant women and partners comprising eight face-to-face sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Educational interventions played an important role in helping women prepare for any eventually and to reconcile the benefits of their actual birth method when it did not correspond to their preference. [ 37 , 40 42 , 44 , 45 , 47 ] Moderate confidence 7 studies, 4 of which had very minor methodological limitations. Data from Europe and the Americas only.…”
Section: Resultsmentioning
confidence: 99%
“…Salomonsson et al (2010) found that midwives perceived supporting women with FOC as emotionally challenging, especially where fear was expressed in a provocative way. The participants in this study did not mention provocation, but on the other hand was taken seriously and respected, it could contribute to a changed attitude towards childbirth (Ramvi & Tangerud, 2011). This might indicate that the woman's motivation for vaginal birth reflects the support and understanding she encountered during pregnancy, in addition to her experience of being in control.…”
Section: Discussionmentioning
confidence: 93%
“…One study describes how women with FOC who were refused a desired CS felt humiliated and ignored in the encounter with healthcare professionals. However, if their story was taken seriously and respected, it could contribute to a changed attitude towards childbirth (Ramvi & Tangerud, ). This might indicate that the woman's motivation for vaginal birth reflects the support and understanding she encountered during pregnancy, in addition to her experience of being in control.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo mostrou que 70% das mulheres não relataram preferência pela cesariana, embora, independentemente do seu desejo, a interação com o serviço de saúde resultou na cesariana como via de parto (8) . Apesar da preferência pelo parto vaginal, evidencia-se que fatores como tabus e medos relacionados à dor, à demora no pré--parto e à experiência negativa da mulher em relação ao parto vaginal anterior favorecem a escolha pela cesariana (9) .…”
unclassified